Analisis Penilaian Resiko Bahaya terhadap Keselamatan dan Kesehatan Kerja pada Proses Pengelolaan Limbah Medis Padat di RSPAD Gatot Soebroto: Hazard Risk Assessment Analysis on Occupational Health and Safety in the Solid Medical Waste Management Process at Gatot Soebroto Army Hospital - Anwar Basuki; Rahmat Supriyatna (MPI Press, 2021)
Introduction: The high number of work accidents in 2016 which reached 0.30% and in 2017 the temporary accident data reached 0.13%, occurred during the stage of solid medical waste management process at Gatot Subroto Hospital. Objectives: The purpose of this study was to determine the level of risk of occupational safety and health hazards to workers at each stage of the solid medical waste management process at Gatot Soebroto Army Hospital. Methods: The method used is analytical descriptive with semiquantitative risk analysis. Results: The results stated that the highest level of risk in the process stage of solid medical waste management is the needle stabbing, which has a risk value of 1500 with Very High Risk and Risk Reduction level of 40%. It should be supervised, training, socialization K3 and introduction safety for employees, and periodic health checks on employees Conclusion: From the results of the study, it was found that the highest level of hazard risk in the solid medical waste management process at the RSPAD was at the risk of needle sticks. The highest level of hazard risk is the risk of needle sticks which has a risk value of 1500 with a Very High risk level.